2015
DOI: 10.1099/jmm.0.000092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a novel lateral-flow device in invasive aspergillosis: a meta-analysis

Abstract: A novel lateral-flow device (LFD) has been invented for use as a diagnostic tool for invasive aspergillosis (IA). We conducted a meta-analysis to assess the diagnostic accuracy of the device. Published studies that used the European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria and provided sufficient data were included. Two reviewers independently collected the data from each study and assessed the risk bias using the Quality Assessment of Diagnostic Accuracy Studies-2. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 28 publications
1
26
0
2
Order By: Relevance
“…Furthermore, in animals with IPA, it is likely that extracellular JF5 mannoprotein antigen released from infectious foci in the lungs accumulates in organs following shedding and circulation in the bloodstream, because the antigen is readily detectable in the serum of neutropenic animals and humans suffering from IPA (34,36,37). The methodology is essentially translatable to humans because the JF5 antibody detects a signature molecule of A. fumigatus infection that is clinically validated for IPA diagnosis in neutropenic patients using bronchoalveolar lavage fluids and point-of-care diagnostics (38). To this end, the antibody has been fully humanized to enable its use in human disease detection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in animals with IPA, it is likely that extracellular JF5 mannoprotein antigen released from infectious foci in the lungs accumulates in organs following shedding and circulation in the bloodstream, because the antigen is readily detectable in the serum of neutropenic animals and humans suffering from IPA (34,36,37). The methodology is essentially translatable to humans because the JF5 antibody detects a signature molecule of A. fumigatus infection that is clinically validated for IPA diagnosis in neutropenic patients using bronchoalveolar lavage fluids and point-of-care diagnostics (38). To this end, the antibody has been fully humanized to enable its use in human disease detection.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis, which included also data from the LFD development study [31] (i.e., in addition to the two studies mentioned above), reported a pooled sensitivity of 68% (95% confidence interval (CI), 52–81%), specificity of 87% (95% CI, 80–92%), and diagnostic odds ratio (DOR) of 11.90 (95% CI, 3.54–39.96) for differentiating proven/probable versus no IA cases in serum samples [37•]. Another very recently published study ignored the recommendations of the manufacturer by using the LFD in serum samples without pretreatment and found poor performance confirming that pretreatment of serum samples is a necessary step and that recommendations of the manufacturer should be followed [38].…”
Section: Introductionmentioning
confidence: 99%
“…Results from the first four-part, retrospective-part, prospective studies (including two multicenter studies) which evaluated the LFD in mostly patients with underlying respiratory diseases [39••] and solid organ transplant recipients [28, 40••, 41] but also a smaller proportion of patients with underlying hematological malignancies [28, 41], were summarized in the meta-analysis reporting a pooled sensitivity of 86% (95% CI, 76–93%), specificity of 93% (95% CI, 89–96%), and DOR of 65.94 (95% CI, 27.21–159.81) for IA when using BALF samples [37]. …”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] New diagnostic methods for the timely identification of IFD have emerged in recent years and are summarized in Table 3. [22][23][24][25][26][27][28] An ideal diagnostic test would be minimally invasive, have a rapid turnaround time to result, be both sensitive and specific for the diagnosis of IFD, differentiate between colonization and invasive disease, and yield speciation and susceptibility data. Clinical trials focused on new diagnostic methods or improvements of existing methods that are currently underway are described in Table 4.…”
Section: Identification and Management Of At-risk Patientsmentioning
confidence: 99%